2021
DOI: 10.3889/oamjms.2021.5729
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Color and Positional Noise on Reading Performance in Human Vision

Abstract: BACKGROUND: Reading can be described as a complex cognitive process of decrypting signs to create meaning. Eventually, it is a way of language achievement, communication, and sharing information and ideas. Changing lighting and color are known to improve visual comfort and the perceptual difficulties that affect reading for those with poor vision. AIM: This study aims to investigate the effect of changing the wavelengths and different levels of positional noise on reading performance for participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 20 publications
3
5
1
Order By: Relevance
“…When introducing positional noise, the reading rate decreased for all wavelengths, and this reduction did not vary with different colors. The findings of the current study were different from our previous study with real words and therefore, unexpected [13], especially for the short wavelength. This means that the effects of colors are varied as varied of cortical processing with different reading types and that was an interesting finding.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…When introducing positional noise, the reading rate decreased for all wavelengths, and this reduction did not vary with different colors. The findings of the current study were different from our previous study with real words and therefore, unexpected [13], especially for the short wavelength. This means that the effects of colors are varied as varied of cortical processing with different reading types and that was an interesting finding.…”
Section: Discussioncontrasting
confidence: 99%
“…This study has shown that the reading speed of non-words was not significantly affected by different wavelengths of light for the participant readers. This is what we expected and consistent with the results of our previous study with changing colors [13]. Furthermore, the mean differences in wpm were reduced more with the long-wavelength compared to with the mid and short wavelengths, with and without positional noise.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations